The Beta Topp-Leone Gumbel Distribution for Modeling the Minimum Flow Data: Atchariya Watthanawisut, Winai Bodhisuwan - Team, Support (Thai Journal of Mathematics, 2020)
In this work a flexible of the Gumbel distribution, called the beta Topp-Leone Gumbel distribution, is introduced. General properties of the distribution are also provided, such as, the linear representation for the probability density function and the cumulative distribution function, transforma- tion, quantile function and moments. The method of maximum likelihood is used to estimate the proposed distribution’s parameters. The applicability of the new distribution is illustrated by the minimum flow dataset.